Measurement and correlation of the vapor–liquid equilibrium for methanol + acetonitrile + imidazolium-based ionic liquids at 101.3 kPa. (October 2016) - Li, Qing; Zhu, Wei; Liu, Bing; Fan, Zenglu; Zhu, Yumeng; Gao, Ziwei
Highlights: Isobaric VLE data for methanol + acetonitrile + imidazolium-IL were studied. The addition of imidazolium-IL could eliminate the azeotropic point of azeotrope. The separation capacity order for imidazolium-ILs is [OMIM][BF4 ] > [EMIM][BF4 ]. All VLE data were correlated with NRTL and UNIQUAC. Abstract: Two imidazolium-based ionic liquids: 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIM][BF4 ]) and 1-octyl-3-methylimidazolium tetrafluoroborate ([OMIM][BF4 ]) were studied as entrainer candidates for the separation of methanol + acetonitrile system. Isobaric vapor–liquid equilibrium (VLE) for the binary methanol + acetonitrile and the ternary mixtures containing imidazolium-based ionic liquids were determined at atmospheric pressure (101.3 kPa). The experimental VLE results indicated ionic liquids (ILs) studied both showed a crossover salting effect for methanol. More importantly, when the amount of IL added increases, the azeotropic point of methanol + acetonitrile will disappear at one specific content. Meanwhile, the separation capacity of imidazolium-based ionic liquids follows the order: [OMIM][BF4 ] > [EMIM][BF4 ]. Finally, two different excess Gibbs free energy models were used to correlate the VLE data: the non-random two-liquid (NRTL), and the universal quasi-chemical (UNIQUAC).